Averaging method in multipoint problems of the theory of nonlinear oscillations - Petryshyn, Ya. R.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By using the averaging method, we prove the solvability of multipoint problems for nonlinear oscillation systems and estimate the deviation of solutions of original and averaged problems.